JAK2, CALR, and MPL mutation spectrum in Japanese patients with myeloproliferative neoplasms - Shogo Shirane; Marito Araki; Soji Morishita; Yoko Edahiro; H. Takei; Yongjin Yoo; Murim Choi; Yoshitaka Sunami; Yasuo Hironaka; Masaaki Noguchi; M Koike; Naohiro Noda; et al. (2014)
JAK2, CALR, and MPL mutation spectrum in Japanese patients with myeloproliferative neoplasmsRecurrent somatic mutations in the JAK2, MPL, and CALR genes have been described in patients diagnosed with Philadelphia-negative myeloproliferative neoplasms (MPN), including polycythemia vera (PV), essential thrombocythemia (ET), and primary myelofibrosis (PMF).These mutations are generally mutually exclusive, and their profiles in different disease entities are diverse.In PV, JAK2 mutations exist in approximately 95% of patients.However, in ET and PMF patients, JAK2, CALR, and MPL mutations are present at frequencies of approximately 60%, 20%, and 5%, respectively. 1To further understand MPN pathogenesis associated with the ET and PMF induced by different gene alterations, classification and epidemiological examination of patients according to gene alterations have been performed.In ET, the CALR mutation is associated with a lower hemoglobin level, higher platelet count, lower leukocyte count, and younger age compared with the JAK2V617F mutation; 2-5 similar characteristics have been observed in PMF patients. 6,7The CALR mutation is also associated with male predominance, 2,5 lower thrombosis risk, 4,6 and better overall survival; 6 however, these characteristics are not always evident and are diverse in some cases.The same gender ratio has been reported in a Chinese cohort of ET patients with JAK2 and CALR mutations. 4The variation between cohorts in the published data most likely reflects different genetic backgrounds in the different ethnic groups that were stud-ied.In addition, because all analyses have been performed in Caucasian populations, with the exception of one study from China, 4 the epidemiological evidence regarding the Asian population is limited.Here, we studied a Japanese MPN cohort that was previously characterized with respect to the JAK2V617F mutation.The cohort consisted of 66 PV, 112 ET, and 23 PMF patients, as defined by the 2008 World Health Organization (WHO) criteria. 8Clinical and laboratory parameters were obtained at the time of first diagnosis or when genomic DNA samples were collected.This study was conducted in accordance with the Declaration of Helsinki and was approved by the ethics committee of Juntendo University School of Medicine (IRB#2012208 and #2013020).All patient specimens that had previously been analyzed for the JAK2 mutation 8 were assessed for CALR and MPL mutations using polymerase chain reaction (PCR)-based assays and subsequent deep-sequencing.In addition, the specimens that exhibited a JAK2V617F mutant allele frequency below 10% in the previous study were re-evaluated via deep sequencing (Online Supplementary Appendix and Online Supplementary Table S1).Re-evaluation identified one PV and 2 ET patients as negative for the JAK2 mutation who a PCR-based assay had previously identified as JAK2V617F-positive with a low allele frequency.Conversely, JAK2 mutations in MPN patients who were negative for JAK2, MPL, and CALR mutations by PCRbased assays were not identified by deep sequencing (see below for MPL and CALR mutation detection).Thus, JAK2 mutations were found in 64 (97%) PV (including 3 exon 12 haematologica 2015; 100:e46 WBC: white blood cell count; RBC: red blood cell count; Hct: hematocrit; Hb: hemoglobin; MCV: mean corpuscular volume.Values with a range are indicated by median values.*A subset of patients was evaluated.**The patients who exhibited mutations in two different genes were omitted.